Caracterización morfológica de hongos fitopatógenos en el cultivo de rosa (rosa sp.), sector Aláquez. Cotopaxi. 2014 - Quimbita Quimbita, Geovanny Patricio (2015)
This research “Morphological characterization of fungal pathogens in rose crop (Rosa sp.) Aláquez. Cotopaxi 2014”, aimed to characterize morphologically phytopathogenic fungus that causes the greatest impact on production in the rose crop (Rosa sp.) in Aláquez Parish, Latacunga Canton in Cotopaxi Province. Laboratory isolation techniques and subsequent observation of the fungus in the Trinocular Microscope CX31 to differentiate parts and ratify the literature were used. Key aspects of this investigation were the determination of the phytopathogenic fungus of greatest impact on the production of rose, it was Botrytis cinerea, also the researcher identified signs and symptoms of the fungus into the field, direct observation and photographic records were used as techniques. Characterized macro-microstructures such as: talo, mycelium, conidiophore and asexual conidia, which their comparison with existing taxonomic keys allowed to confirm the presence of the causative agent is Botrytis cinerea, it could describe its life cycle under controlled conditions making planting and insolation of the pathogen in Petri dishes on a PDA culture medium, with a last of four days at 22°C temperature in an incubation chamber. The product of this research has been consolidated into a tutorial of the morphological characteristics of the fungus studied in order to socialize the results obtained.